LEGAL PROTECTION OF CREDITORS RELATED TO COLLECTIVE RIGHTS ON LAND THAT HAVE NOT BEEN CERTIFIED AS A RESULT OF THE PROCESS OF REGISTRATION OF LAND RIGHTS HAS NOT BEEN COMPLETED - Hera Widjayanti (JILPR Journal Indonesia Law and Policy Review, 2023)
Legal protection for creditors regarding their existenceMortgage rights over land that have not been certified as a result of the process of registering land rights that have not been completed, and using normative juridical research types with statutory approaches and conceptual approaches. The results of this study conclude that the results of the research show that the legal consequences of the registration of land rights that have not been completed (hereinafter referred to as apht) to bank credit agreements made by the parties before a notary/official making land deeds (hereinafter referred to as ppat) is that the creditor does not have aa priority position . Where is the form of legal protection that can be given to creditors as a form of anticipation. The creditor's right to collateral in the event that the apht is not completed, that is, does not give precedence rights compared to other creditors. The purpose of imposing mortgage rights is to provide legal protection and certainty to all parties (especially creditors) and also to fulfill the principle of publicity. Article 1 paragraph (1) of the law on mortgages regulates provisions regarding the granting of mortgage rights from debtors to creditors in respect of debts secured by mortgage rights. The granting of this right is intended to give priority to the creditor concerned (preferred creditor) over other creditors. Thus the granting of a mortgage is a guarantee for repayment of the debtor's debt to the creditor in connection with the loan/credit agreement in question. Mortgage rights will not arise without APHT registration. The conclusion in this study is that legal protection is all kinds of activities carried out to provide a safe, comfortable and lawful environment. To guarantee legal certainty and defend the rights of creditors in granting credit, all efforts must be made in providing legal certainty and fair agreements between creditors and debtors such as preventive and repressive legal protection.